2016
DOI: 10.1080/09286586.2016.1212991
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Visual Outcomes of Cataract Surgery in Rural South India: A Cross-Sectional Study

Abstract: The high prevalence of avoidable causes of visual impairment in this rural setting indicates the scope for preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Such reports are, however, more than a decade old when visual outcomes of cataract surgery were poor, and majority had aphakia. However, more recent population-based studies as well as SSU data[ 10 ] report the prevalence of good visual outcomes (>6/18 BCVA in operated eye to be above 75%),[ 23 29 ] indicating an overall improvement in quality and outcomes of cataract surgery over time. Since patients with good outcomes can be powerful motivators;[ 19 ] this positive trend needs to be continued and further improved by quality control measures by cataract surgery providers.…”
Section: Discussionmentioning
confidence: 99%
“…Such reports are, however, more than a decade old when visual outcomes of cataract surgery were poor, and majority had aphakia. However, more recent population-based studies as well as SSU data[ 10 ] report the prevalence of good visual outcomes (>6/18 BCVA in operated eye to be above 75%),[ 23 29 ] indicating an overall improvement in quality and outcomes of cataract surgery over time. Since patients with good outcomes can be powerful motivators;[ 19 ] this positive trend needs to be continued and further improved by quality control measures by cataract surgery providers.…”
Section: Discussionmentioning
confidence: 99%
“…1 In India, the prevalence of age related cataract is extremely high necessitating a large number of cataract surgeries. 5,6 India is now the diabetic capital of the world with other comorbidities trailing not far behind. [7][8][9] A large proportion of patients (almost 50%) undergoing cataract surgery in India are found to have co-morbidities like diabetes, hypertension, CKD, COPD, bronchial asthma and seizure disorder.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A better visual outcome is achieved with fewer intraoperative complications in outreach camps where surgeries will be done at base hospital. 11 This study aims to find out effectivity of outreach camps in reducing the burden of cataract-related blindness.…”
Section: Discussionmentioning
confidence: 99%
“…A poor visual outcome has been reported in 15-25%of eyes following cataract surgery (1999); 13 another recent report (2016) by Paul et al and Senjum et al (2009-13) his suggestive of poor visual outcome in 8.8% and 9.4% cases respectively. 11,14 A study from central India (2011) revealed the need for improved surgical technique and improved IOL power calculation may markedly improve the visual outcome as 2 out of 3 eyes in their cohorts had poor postoperative visual outcome. 8 So we emphasized the accuracy of IOL power calculation and improving the quality of surgery to rectify this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation